Specific absorption rate and path loss in specific body location in heterogeneous human model. Issue 1 (1st January 2013) - Kurup, Divya; Joseph, Wout; Vermeeren, Günter; Martens, Luc
Abstract : A multi‐implant scenario is considered using insulated dipole antennas for specific locations such as the liver, heart, spleen and the kidneys where implants communicate with a pacemaker acting as a central hub. Wireless communication within human body experiences loss in the form of attenuation and absorption, and to identify these losses, the path loss is studied in this paper for an adult and child heterogeneous human model. Link performance is calculated to investigate the applicability of in‐body communication. The specific absorption rate for all these locations is also studied to verify compliance with international safety guidelines.